Bambara Groundnut (Vigna subterranea L. Verdc): a crop for the new millennium, its genetic diversity, and improvements to mitigate future Food and nutritional challenges - Khan, Md Mahmudul Hasan; Yusop, Mohd Rafii; Ramlee, Shairul Izan; Jusoh, Mashitah; Md Al-Mamun (Multidisciplinary Digital Publishing Institute, 2021)
The world’s food and agricultural schemes have gradually fallen into an alarming state due to challenges such as high population birth rates, diverse agro-climatic zones, a lack of measures to counter global warming, severe practices of sole-culture cultivation, and asset reduction. A very high dependency on limited staple food crops is associated with repetitious diets, deprivation of food, and shortages of trace minerals, which often causes dietary sicknesses. To ensure nutritious diets worldwide, a real-world and justifiable scheme is provided to garner extra attention towards variation in both agriculture/farming approaches and food habits. The EAT-Lancet statement emphasized an increase in agri-based diets as a way of attaining global generational health. Enlarging neglected crops with plenty of genomic stocks and potentially profitable attributes is a solution that could address food and nutritional security concerns. Bambara groundnut is one such imperative and neglected legume crop that contributes positively to improving global food and nutrient safety. As a “complete food”, this crop has recently been treated as a new millennium crop, and furthermore, it is more adjusted to poor soil and climatic conditions than other dominant crops. Bambara groundnut is a repository of vital nutrients that provides carbohydrates, crucial amino acids, proteins, and energy as well as minerals and vitamins to developed and low-income countries where animal proteins are not readily available. This review explores the potential of Bambara groundnut in ensuring food and nutrient security; its variables, production, processing, nutrient values, role in reducing the nutritional gap, and diverse uses; and attempts in improving its traits. To strengthen food production, an agricultural revolution is required for underutilized crop species to feed the ever-expanding population in the world. Henceforth, advanced plant-breeding procedures, such as next-generation breeding techniques, various molecular tools, TILLING, Eco-TILLING, proteomics, genomics, and transcriptomics (which has been used for major crops), also need to be practiced to intensify production. To boost productivity and to feed the most starved and malnourished populations of the world, it is assumed that the application of modern techniques will play a vital role in the advancement of the underutilized Bambara groundnut.